Renal dysfunction contributes to deteriorated survival outcomes in patients with upper and lower gastrointestinal bleeding: insights from a cohort study of 1160 cases - Orsolya Anna Simon; Levente Frim; Nelli Farkas; Zoltán Sipos; Nóra Vörhendi; Eszter Boros; Dániel Pálinkás; Brigitta Teutsch; Patrícia Kalló; Vivien Vass; Andrea Szentesi; Roland Hágendorn; et al. (Scientific Reports)
Abstract Both acute kidney injury and chronic kidney disease are risk factors for many outcomes of gastrointestinal bleeding (GIB). These are associated with higher mortality, longer hospitalisation, and greater need for transfusion in case of overt GIB. Our study aimed to further evaluate the role of kidney function in several clinical outcomes of GIB patients. The Hungarian Gastrointestinal Bleeding Registry collected data on all-cause GIB between 2019 and 2022. A multi-level data-validation system provided high-quality data, which was retrospectively analysed. Numerous primary (in-hospital mortality, discharge, need for endoscopic intervention, in-hospital rebleeding, length of hospitalisation, need for emergency surgery, need for endoscopic examination and need for intensive care unit) and secondary (detection of Helicobacter pylori (H. pylori), recognition of cancer as the source of bleeding, need for any kind of transfusion or clotting factor, anticoagulation therapy) outcomes were observed. Descriptive statistical tools were used to summarize our data. Among others, estimated glomerular filtration rate (eGFR) (ml/min/1.73 m2) was used as continuous variable, mean, standard deviation, median, interquartile range and minimum/maximum values were calculated. Reduced kidney function was associated with in-hospital mortality (eGFR: 42.63 ± 28.78 ml/min/1.73 m2 vs. 57.08 ± 26.62 ml/min/1.73 m2, p < 0.001), need for red blood cells (RBC) transfusion (eGFR: 51.98 ± 27.90 ml/min/1.73 m2 vs. 60.11 ± 25.06 ml/min/1.73 m2, p < 0.001) and clotting factor supplementation (eGFR: 47.40 ± 27.41 ml/min/1.73 m2 vs. 56.68 ± 27.02 ml/min/1.73 m2, p < 0.001). Better eGFR values at admission were associated with discharge home after proper treatment, compared to any other outcome of the admission (eGFR: 58.12 ± 25.56 ml/min/1.73 m2 vs. 50.23 ± 29.69 ml/min/1.73 m2, p < 0.001), H. pylori positivity (eGFR: 59.63 ± 25.24 ml/min/1.73 m2 vs. 52.76 ± 25.44 ml/min/1.73 m2, p = 0.021) and the need for endoscopic intervention (eGFR: 58.65 ± 26.61 ml/min/1.73 m2 vs. 54.31 ± 27.64 ml/min/1.73 m2, p = 0.008). At admission, patients with better eGFR than 36.64 ml/min/1.73 m2 were discharged to their homes, mortality was higher with eGFR worse than 25.96 ml/min/1.73 m2, more RBC transfusion was needed if eGFR was lower than 49.61 ml/min/1.73 m2. Regulation of anticoagulation was examined extensively. Impaired kidney function at admission results higher in-hospital mortality in overt all-cause GIB and increases the need of RBC transfusion.